Sónia Frota & Pilar Prieto (eds.), Intonation in Romance. Oxford University Press, Oxford, 2015; 400 pp. - Villalobos Pedroza, Laura Cristina (El Colegio de México, 2017)
Se reseñó el libro: Intonation in Romance.